From Stress To Exit: The Role Of Workplace Incivility In Shaping Turnover Intentions Among Indonesian Gen Z - Daffa Abhinaya Putra; Thea Geneveva Josephine Jesajas; Puty Febriasari (SEAN Institute, 2024)
The phenomenon of job stress and workplace incivility has become increasingly prominent in modern organizational settings, significantly affecting employee well-being and organizational outcomes. Understanding these dynamics is particularly crucial for Generation Z, who are now entering the workforce in large numbers. This study aims to analyze the impact of job stress and workplace incivility on turnover intention among employed Generation Z individuals in Indonesia. Data were collected from 280 Gen Z respondents and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that both job stress and workplace incivility have a notable and positive impact on turnover intention. Specifically, higher levels of job stress and workplace incivility lead to an increased intention among Gen Z employees to leave their jobs. These findings underscore the importance for companies to address stress and incivility in the workplace to reduce turnover rates among Gen Z employees, thereby enhancing organizational stability and performance.